The Modern Information Technologies and Visualization Methods for Analysis of Computer Simulation Results for Complex Plasma (Communications in Computational Physics, 2020)
In this paper we present a software package based on modern informationtechnologies that allows rapid analysis and visualization of the properties of complexplasmas. The properties of plasma are simulated by two means. First of all, wehave applied the molecular dynamics simulation method which numerically solves theequations of motions for plasma particles. Secondly, we calculate microscopic propertiesof plasma by using the Boltzmann equation with additional relations, initial andboundary conditions.